factors affecting on women entrepreneurial intention: A study on Sudanese entrepreneurial women - Hamid, Abdelsalam; Bashir Biraima, Mohammed Ahmed; El- khidir, El Sheikh Mohammed (FEB - Universitas Lampung, 2022)
Purpose: this study aims to test the factors affecting on women entrepreneurial intention. The study relied on the theory of planned behaviour to interpret the entrepreneurial intention. Methodology; based on the descriptive methodology the study tested the factors of women entrepreneurial intention. The data for this study has been collected by survey from a anon-probability purposive sampling methods the sample size was 251 respondents of Sudanese entrepreneurial women in Khartoum state. The data collected from the responds was prepared and analyzed; by SPSS; software AMOS; Findings; the results of the study showed that entrepreneurial attitude; has a significant positive effect on entrepreneurial intention, risk-taking propensity; has no significant positive on entrepreneurial intention and creativity has no significant on entrepreneurial intention. Implications for theory and practice; from a practice point of view, the study tested how Sudanese women’s entrepreneurial attitude; risk-taking propensity; and creativity can develop entrepreneurial intention. Originality and value; the main contribution of the study is forming the combination of the factors affecting on women’s entrepreneurship and entrepreneurial intention among Sudanese women entrepreneurs.